Wage Rigidity: A Quantitative Solution to Several Asset Pricing Puzzles - Favilukis, Jack; Lin, Xiaoji (Review of Financial Studies, 2016)
In standard production models, wage volatility is far too high, and equity volatility is far too low. A simple modification–sticky wages because of infrequent resetting together with a constant elasticity of substitution (CES) production function leads to both smoother wages and higher equity volatility. Further, the model produces several other hard-to-explain features of financial data: high Sharpe ratios, low and smooth interest rates, time-varying equity volatility and premium, a value premium, and a downward-sloping equity term structure. Procyclical, volatile wages are a hedge for firms in standard models; smoother wages act like operating leverage, making profits and dividends riskier. Received July 30, 2013; accepted July 6, 2015 by Editor Geert Bekaert.